2014
DOI: 10.1007/s10916-014-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis and Improvement of Yan et al.’s Biometric-Based Authentication Scheme for Telecare Medicine Information Systems

Abstract: Remote user authentication is desirable for a Telecare Medicine Information System (TMIS) for the safety, security and integrity of transmitted data over the public channel. In 2013, Tan presented a biometric based remote user authentication scheme and claimed that his scheme is secure. Recently, Yan et al. demonstrated some drawbacks in Tan's scheme and proposed an improved scheme to erase the drawbacks of Tan's scheme. We analyze Yan et al.'s scheme and identify that their scheme is vulnerable to off-line pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
88
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 31 publications
0
88
0
Order By: Relevance
“…But, the researchers have considered biometric feature [2] with the password to enhance the security label. Therefore, many researchers have proposed biometric and password based authentication schemes in [17][18][19][20][21][22][23][24][25][26][27][28]. Li and Hwang [17] proposed a biometrics-based remote user authentication scheme in 2010.…”
Section: Literature Surveymentioning
confidence: 99%
See 4 more Smart Citations
“…But, the researchers have considered biometric feature [2] with the password to enhance the security label. Therefore, many researchers have proposed biometric and password based authentication schemes in [17][18][19][20][21][22][23][24][25][26][27][28]. Li and Hwang [17] proposed a biometrics-based remote user authentication scheme in 2010.…”
Section: Literature Surveymentioning
confidence: 99%
“…But, Yan et al [23] pointed out that Tan's scheme [22] is vulnerable to the Denial-of-Service (DoS) attack. However, recently, Mishra et al [24] showed that Yan et al's scheme [23] suffers from off-line password guessing attack and has inefficient login and password change phases. Huang et al [29] proposed an authentication scheme based on RSA.…”
Section: Literature Surveymentioning
confidence: 99%
See 3 more Smart Citations